Desain dan Implementasi Web Pemesanan Makanan untuk Mempercepat Proses Antrean Pelanggan - Rifqi Putra Winanda; Nazwa Salsyabilla Ramadhani; Repi Meilani Putri; Nuriana Sipahutar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Lengthy, disorganized physical queues in conventional food ordering systems, particularly within canteens, significantly compromise customer convenience and operational efficiency. This direct-ordering model often results in crowd congestion, unpredictably long waiting times, and potential friction among patrons. To address these operational issues and substantially enhance user satisfaction, this research proposes the development and implementation of an innovative Web-Based Food Ordering System. This digital platform allows customers to place orders entirely online, effectively eliminating the need for physical queuing. The system's core functionality is the realtime monitoring of order status and queue position, providing transparent information directly to the customer's device. For canteen management, the application offers a crucial tool for integrated and structured order handling, ensuring staff can prepare meals more accurately and promptly. By transforming the ordering process into a streamlined digital workflow, the system is expected to accelerate the service cycle, minimize unnecessary crowding, and substantially improve customer satisfaction through a modernized, well-organized, and highly efficient experience. This initiative represents a significant step toward smarter and more responsive food service operations.